Age and Sex Influence Thyroid Hormone Effects in Target Tissues with Organ-Specific Responses - Kerp, Helena; Gassen, Janina; Führer, Dagmar (Experimental and Clinical Endocrinology & Diabetes, 2020)
Age and sex impact prevalence and clinical features of thyroid disease. Thyroid dysfunction occurs with a higher frequency in elderly patients and females. Moreover, age alters clinical presentation of hyper- and hypothyroidism and onset of thyroid hormone (TH) related co-morbidities leading to increased risk for underdiagnosis and maltreatment in the elderly. Rodent models allow further insights into mechanisms of age- and sex-dependent TH action in target tissues. In this review, we summarize findings from mouse studies showing distinct effects of age and sex on systemic versus organ-specific TH action and discuss their wider implication for clinical care.
Keywords: age; sex; thyroid hormones; mouse models